A Correlational Study On Internal Control System Efficiency And Operational Sustainability Of Selected Savings And Credit Cooperatives In The Camanava Area Of Metropolitan Manila (International Journal of Scientific Research and Management (IJSRM), 2018)
The research delved on determining the relationship between internal control system efficiency and operational sustainability of selected savings and credit cooperatives in CAMANAVA Area, Metropolitan Manila, Philippines. The descriptive research method was utilized employing both quantitative and qualitative approaches. Survey questionnaires, in-depth personal interview, and focused group discussions (FGDs) were used to gather relevant data from selected employees/staff, committee members and executive officers of the subject savings and credit cooperatives. Quantitative data were statistically processed using Analysis of Variance (ANOVA) and Pearson Correlation Coefficient (Pearson’s r). Qualitative data were coded, patterns and relationships analyzed, and findings summarized into themes. The result of the study revealed that the internal control system of savings and credit cooperatives specifically in terms of the control environment, risk assessment, information and communication, control activities, and monitoring have a strong relationship with the cooperatives’ operational sustainability, particularly in political, economic, social, technological, and legal aspects. The study further revealed that the cooperatives face certain problems in the areas of employee recruitment and selection, innovation, credit investigation, and complaints handling.